Implementation of the Sapta Pesona Concept and Community Participation in Riam Tinggi Village, Delang Sub-District, Lamandau District, Central Kalimantan - Marantina*, Cicik; Christa, Usup Riassy; Isfarudi, Isfarudi (Riwayat: Educational Journal of History and Humanities, 2023)
The natural beauty of Riam Tinggi Village, Delang District, made the village receive an award from the Indonesian Tourism Village Award Program in 2021. Reported in the Central Kalimantan Statistics Agency (BPS) that the length of stay of tourists in the Province, including in Riam Tinggi Village is quite low, which is not more than two nights. This can be overcome one of them by applying the elements of Sapta Pesona and the commitment of the community to participate in its implementation. The purpose of this study was to determine how the implementation of Sapta Pesona in Riam Tinggi Village and to determine the participation of the Riam Tinggi Village community in the implementation of Sapta Pesona. This research uses a descriptive method with a qualitative approach. Questionnaires were distributed to tourists who had visited Riam Tinggi Village for tourism in the past month, as well as the people of Riam Tinggi Village .